Meeting notes from the 3rd IAS Conference. Treating TB and HIV concurrently. - Friedland, Gerald H (AIDS clinical care, 2005)
Several IAS reports focused on strategies for overcoming reduced levels of nevirapine due to rifampin coadministration.
Keywords: Brazil; Congresses as Topic; Drug Therapy, Combination; HIV Infections; Humans; Nevirapine; Rifampin; Tuberculosis